Final answer:
The inverse of the function y = 3x + 4 is y = (x - 4) / 3.
Step-by-step explanation:
The inverse of a function is a different function that, when applied to the output of the original function, gives back the original input. In simpler terms, if you have a function that relates input values to output values, the inverse function does the opposite, mapping the output values back to the original input values.
The inverse of the function y = 3x + 4 is y = (x - 4) / 3.
To find the inverse of a function, we need to swap the x and y variables and solve for the new y.
Step 1: Replace y with x and x with y: x = 3y + 4.
Step 2: Solve for y: x - 4 = 3y.
Step 3: Divide both sides by 3: (x - 4) / 3 = y.
Therefore, the inverse of the function y = 3x + 4 is y = (x - 4) / 3.